Exploring the Potential of Mangrove Leaf Extracts as Natural Preservatives for Protein-Rich Fish: Evidence from Chanos chanos - Ranulfo Friolo Cala; Rodeon Durotan; Mudrikatul Asna (Journal of Academic Biology and Biology Education, 2025)
Purpose of the study: This study aims to analyze the effect of ethanolic extract of Rhizophora mucronata leaves at different concentrations and preservation times on the protein content of milkfish (Chanos chanos), to determine the optimal extract concentration for maintaining protein quality during storage. Methodology: This study used an experimental laboratory design with milkfish (Chanos chanos) treated using ethanolic extracts of Rhizophora mucronata leaves. Tools included a rotary evaporator (IKA RV 10), analytical balance (Ohaus Pioneer), freeze dryer (Labconco), and Kjeldahl apparatus (Velp Scientifica). Protein analysis followed AOAC (2005) using SPSS v26 for Two-Way ANOVA. Main Findings: The study found that increasing concentrations of ethanolic extract of Rhizophora mucronata leaves led to higher protein content in milkfish (Chanos chanos). The highest protein level was observed at 50 ppm concentration with 12-hour preservation. Two-Way ANOVA showed significant effects of concentration and time individually, but no significant interaction between the two factors (P = 0.148 > 0.05). Novelty/Originality of this study: This study is the first to evaluate the effect of Rhizophora mucronata ethanolic leaf extract on the protein content of milkfish (Chanos chanos) under Philippine conditions. It introduces a natural, eco-friendly preservation approach, advancing current knowledge on the use of mangrove bioactive compounds to maintain fish protein quality during post-harvest storage.